Italian Polyptych of the Late 15th – Early16th Centuries: Renaissance Form and Pre-Renaissance Ways of Creating Meaning - Nazarova, Olga A. (Actual Problems of Theory and History of Art, 2024)
The altar polyptychs of the end of the 15th – first half of the 16th centuries, as a rule, remain on the periphery of the study of Renaissance art, overshadowed by the altarpieces of the new Renaissance pala quadra type. Nevertheless, the late polyptychs, produced in various centers outside Florence (Umbria, Rome, Northern Italy, Liguria), are often impressive art-works by leading artists, commissioned by prominent patrons. This indicates that the polyptych, as a form of altarpiece with its specific ways of constructing meanings, which avoid direct narrative and are based on a visual confrontation of themes and images located in different parts of the work, remained in demand among patrons and different audiences and required the preservation of a multi-part structure of altarpiece. The new visual language of the Italian Renaissance art, with its emulation of ancient architectural and ornamental forms, perspective space constructions, the use of figurative elements, and techniques of Transalpine painting, has traditionally  been considered incongruent with the multi-part structure of the polyptych, which originated in the Gothic era in the late 13th – early 14th centuries. Based on the analysis of selected late altarpieces in the form of polyptychs, the paper outlines the transformation of the polyptych into a genuinely Renaissance phenomenon, making the most of Renaissance artistic means and putting them to its service, adapting it to the new aesthetics, but preserving its multi-paneled structure and thus its ancient semantic possibilities.
Keywords: Renaissance altarpiece; Renaissance polyptych; Italian Renaissance painting